Transitional justice theories - Buckley-Zistel, Susanne; Koloma Beck, Teresa; Braun, Christian; Mieth, Friederike (Transitional justice, 2014)
"Transitional justice has gained global significance as an umbrella term for approaches to dealing with the past in the aftermath of violent conflict or dictatorial regimes; a range of mechanisms and institutions, including tribunals, truth commissions and memorial projects seek to redress past wrongs, vindicate the dignity of victims, and provide justice. Despite this global activity and the lively academic debate surrounding it, there have been few attempts to conceptualize transitional justice theoretically. Transitional Justice Theories therefore seeks to deliver a hitherto absent theoretical framework by exploring both normative and critical perspectives from disciplines such as political science, sociology, philosophy, or psychology. Working through such concepts as the social processes of the transitional moment and the differing perspectives on justice (as potentially restorative, transformative, and reparative), this volume highlights the field's interdisciplinary scope while revealing the commonalities, as well as tensions, between the various perspectives. Contributing to the academic debate as well as to the practice of transitional justice, this book is an important contribution to a dynamic field. As such, it will be of immense interest to scholars, students, and practitioners of transitional justice, and more widely of Law, Politics, and Sociology"--